2021
DOI: 10.1101/2021.12.03.469332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tibial nerve stimulation increases vaginal blood perfusion and bone mineral density and yield load in ovariectomized rat menopause model

Abstract: Human menopause transition and post-menopausal syndrome, driven by reduced ovarian activity and estrogen levels, are associated with an increased risk for symptoms including but not limited to sexual dysfunction, metabolic disease, and osteoporosis. Current treatments (both hormonal and non-hormonal) are limited in efficacy and may have adverse consequences, so investigation for additional treatment options is necessary. Previous studies have demonstrated that tibial nerve stimulation or electro-acupuncture ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Stimulation delivered in sessions repeated across a long-term interval could be continually improving genital blood flow, leading to more positive sexual experiences for female rats. Recently we showed that tibial nerve stimulation after ovariectomy can maintain vaginal blood flow increases for several weeks but not to six weeks 12 , aligning with findings of this study that hormone priming may also be needed for longterm benefits. Electrical stimulation may strengthen the spinal circuit for sexual function or may lead to cortical changes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Stimulation delivered in sessions repeated across a long-term interval could be continually improving genital blood flow, leading to more positive sexual experiences for female rats. Recently we showed that tibial nerve stimulation after ovariectomy can maintain vaginal blood flow increases for several weeks but not to six weeks 12 , aligning with findings of this study that hormone priming may also be needed for longterm benefits. Electrical stimulation may strengthen the spinal circuit for sexual function or may lead to cortical changes.…”
Section: Discussionsupporting
confidence: 90%
“…We delivered stimulation at twice the motor threshold with biphasic, 20 Hz, 200 μs pulsewidth stimulation for 30 minutes. We used these stimulation parameters to mimic parameters used in rat studies investigating the effect of tibial nerve stimulation on both sexual 10,12 and bladder functioning. 24,25…”
Section: Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaginal blood flow gradually increased, peaked, and gradually returned to baseline lasting for 15 seconds to two minutes. Preclinical experiments have also demonstrated the potential for tibial nerve stimulation to modulate vaginal blood flow 23,44 and that estrogen is necessary to preserve this response 44 . We expected to see similar responses in perineal blood perfusion in our experiments, but neither pudendal nor tibial nerve stimulation had an effect on perineal blood perfusion that persisted beyond the stimulation epoch.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord transection did not change the lack of response. Researchers have previously found that vaginal blood flow, measured with LDF, can increase in response to tibial nerve stimulation 23,44 . The absence of blood perfusion changes in these experiments could be attributed to a difference in recording areas (vagina vs vulva), just as in pudendal nerve stimulation trials.…”
Section: Discussionmentioning
confidence: 99%